2021
DOI: 10.1093/eurheartj/suab098
|View full text |Cite
|
Sign up to set email alerts
|

Does sacubitril/valsartan work in acute myocardial infarction? The PARADISE-AMI study

Abstract: Patients with acute myocardial infarction (AMI) complicated by left ventricular dysfunction have an increased risk of death and heart failure. Numerous clinical studies have demonstrated the ability of ACE inhibitors in optimizing the outcome in this particular clinical setting. In recent years, the sacubitril/valsartan association has drastically improved the prognosis of patients with heart failure with reduced ejection fraction with a significant decrease in mortality from cardiovascular causes and hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…It not only promotes the activity of natriuretic peptide to expand blood vessels, excrete sodium, and induce diuresis, it also inhibits profibrotic signaling markers to function in cardiac failure. This inhibition helps to protect the kidneys (24). Valsartan is a kind of common anti-high blood pressure drug, which is used as an inhibitor of the angiotensin II receptor.…”
Section: Discussionmentioning
confidence: 99%
“…It not only promotes the activity of natriuretic peptide to expand blood vessels, excrete sodium, and induce diuresis, it also inhibits profibrotic signaling markers to function in cardiac failure. This inhibition helps to protect the kidneys (24). Valsartan is a kind of common anti-high blood pressure drug, which is used as an inhibitor of the angiotensin II receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In the PIONEER-HF trial, early treatment of lcz696 in patients with MI reduced the level of N-terminal pro-B-type natriuretic peptide and alleviated LV systolic dysfunction [ 24 ]. The PARADISE-AMI study also showed that patients with acute MI benefit from the lcz696 treatment [ 25 ], and studies are emerging to analyze the treating effect of lcz696 on MI and heart failure [ 15 , 26 ]. Moreover, several studies reported that the molecular changes are involved in the biofunctions of lcz696.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of ARNI in patients with acute MI were studied in the PARADISE–MI study, which compared sacubitril/valsartan with ramipril in patients with acute MI and with an LV EF < 40% and/or signs of pulmonary congestion. The results of this study showed that sacubitril/valsartan did not reduce cardiovascular death or first HF hospitalization, compared to ramipril, however, it had a clear benefit in all HF events [ 152 , 153 ]. Moreover, in a recent meta-analysis, Zhang et al showed that sacubitril/valsartan therapy after MI prevents adverse ventricular remodeling, thus improving cardiac function and reducing the rate of adverse cardiovascular events [ 149 ].…”
Section: Therapeutic Implications In Adverse Cardiac Remodelingmentioning
confidence: 99%